Inhibition of neutral sphingomyelinase 2 promotes remyelination - Yoo, Seung-Wan; Agarwal, Amit; Smith, Matthew D.; Khuder, Saja S.; Baxi, Emily G.; Thomas, Ajit G.; Rojas, Camilo; Moniruzzaman, Mohammed; Slusher, Barbara S.; Bergles, Dwight E.; Calabresi, Peter A.; Haughey, Norman J. (Science advances, 2020)
Myelination requires a highly organized synthesis of multiple lipid species that regulate myelin curvature and compaction. For reasons that are not understood, central nervous system remyelinated axons often have thin myelin sheaths with a disorganized structure susceptible to secondary demyelination. We found that expression of the sphingomyelin hydrolase neutral sphingomyelinase 2 (nSMase2) during the differentiation of oligodendrocyte progenitor cells (OPCs) to myelinating oligodendrocytes changes their response to inflammatory cytokines. OPCs do not express nSMase2 and exhibit a protective/regenerative response to tumor necrosis factor-α and interleukin-1β. Oligodendrocytes express nSMase2 and exhibit a stress response to cytokine challenge that includes an overproduction of ceramide, a sphingolipid that forms negative curvatures in membranes. Pharmacological inhibition or genetic deletion of nSMase2 in myelinating oligodendrocytes normalized the ceramide content of remyelinated fibers and increased thickness and compaction. These results suggest that inhibition of nSMase2 could improve the quality of myelin and stabilize structure. - Targeting a sphingomyelin hydrolase improves the structure of remyelinated fibers in a mouse model of multiple sclerosis. - Targeting a sphingomyelin hydrolase improves the structure of remyelinated fibers in a mouse model of multiple sclerosis.